Green finance in Bangladesh: Policies, institutions, and challenges - Monzur Hossain (Asian Development Bank Institute (ADBI), 2018)
This paper provides an overview of Bangladesh's green financing status, with a particular focus on the renewable energy (RE) sector. Despite having great potential of renewable energy sources, the sector currently consists of a meager 1% share of the energy portfolio. The poor performance of the renewable energy sector is attributable to factors such as the lack of the required technology, a regulatory and institutional framework, and proper policies and incentives. This paper discusses both the potential for and the impediments to expanding renewable energy projects. Though the Bangladesh Bank has formulated green banking guidelines, the lack of capacities of banks and financial institutions, the lack of a proper understanding of the risks and returns of green projects, and the underdeveloped equity and bond markets hamper the expected growth of green projects in Bangladesh. As a case study, the paper analyzes various aspects of a successful Solar Home System program, which the Infrastructure Development Company Limited (IDCOL) implemented, to understand the risks and potential of a renewable energy project. The IDCOL's solar homes program in Bangladesh, which has installed 4.13 million solar home systems so far, almost 90% of the total, is a good example of a public-private partnership in green financing. However, this successful program is now on the brink of abandonment due to huge amount remaining default with the customers which is attributed to several reasons such as uncoordinated grid electricity expansion, a lack of coordination among the respective agencies, the failure of the program's commercialization, poor financial governance, and the absence of a national policy oversight body. Therefore, the capacity building of banks and financial institutions, the development of bond and equity markets, a well-coordinated policy oversight body, and mainstreaming green finance are some of the key policy issues that Bangladesh needs to address to promote green financing and achieve sustainable development.
Keywords: Q41; Q42; Q43; Q47; Q48; 330; green finance; energy security; renewable energy technology; subsidy; Bangladesh